Factors that Build Loyalty to Digital Press Websites in Ecuador - Antepara-Basurto, José; Braganza, Luis; López, Wilman (Revista Ecos de la Academia, 2021)
The aim of the present work is analizing the main factors that could affect the loyalty to digital newspapers. Specifically, effects triggered by the degree of web site usability, the reputation and familiarity to the web site, those are moderated by the education level. The mediator effect on factors as satisfaction and trust on a web site that deal with those relationhips on lotalty were also analized. Methodology: One hundred and forty two cases were studied for the experimental study, the proposed hypothesis were contrasted using the structural equations modeling technique. Results: The rely on had a significative effect, generating a positive impact as the revisiting intention, and a partial mediator effect in the Intendedness-Satisfaction relation for revisiting the site and on the Intendedness-Satisfaction relation for recommending it. Reputation, usability and familiarity had impact on satisfaction. Conclusions: The following three final aspects have been recorded: (1) For customers, reputation is more important tan usability and familiarity; (2) the higher education is correlated to the satisfaction from usability; and, (3) the rely on mediator effect is basic for customers during the process of loyalty building.